Gotycka rzeźba Ukrzyżowanego Chrystusa ze Starogardu Gdańskiego - Błażejewska, Anna (Sztuka i Kultura, 2021)
The sculpture of Crucified Christ (about 2 metres high) was found by Michał Walicki in 1933 in a church in Starogard Gdański. The founder recognized it as an ‘outstanding’ artwork, dating back to the beginning of 14th century or ca. 1320, connecting archaic traits of Romanesque art (type of head, positioning of the body) with the features of Gothic crucifixes. That complex character of the artwork impeded its more precise recognition (workshop, dating). That is certainly why, in spite of its high rank, the crucifix did not come to be a popular research subject. Later references of art historians are nothing but brief mentions (except a modest monograph by Anita Cylkowska), reiterating, complementing or somewhat modifying the theses put forward by Walicki (A. Cylkowska, for instance, shifted the dating to ca. 1350–1370). It was only Karl-Heinz Clasen who came forth with a wholly different hypothesis – he linked the title crucifix with the so-called Prussian Madonnas on a Lion circle (among others he pointed to the Madonna of Lubieszewo as a stylistic kin) and dated it to the last quarter of 14th century. It is worth returning to that forgotten thesis, for it seems well founded. The almost stiffly straightened positioning of the body is not an archaic, Romanesque trait; this kind of crucifixes can be found in the second half of 14th century, especially in painting (Crucifixion, Emaus monastery in Prague, ca. 1360, Crucifixion, a quarter of the Grudziądz altar, the end of 14th century, a wall painting in a Church of the Minorities in Stein in Austria, ca. 1350). Some of the examples (Stein) are typologically very close to the Stargard piece (leg positioning, the layout of loincloths). Similarly, as regards the details of sculpting work: the way the head, the hair and the loincloths were made. Here one could indicate more specific artistic inspirations. The shape of the head, the expressive moulding of the face (prominent nose, hard line of the lips), the hair arranged in wide, ‘ribbon-like’ strands, bear numerous resemblances to the leading artworks of the Madonnas of a Lion circle, both from Silesia (the Apostles of Wrocław, the altar figures of Bąkowo), as well as the Prussian ones (Apostles’ heads from the altar of Kraplewo near Ostroda, that of the Christ from the Triumph of Mary group from Lalkowy near Gdańsk, the undefined apostle from the church in Dzierzgoń, or the Sorrowful Mary from the altar of Virmo in Finland – imported from Prussia, etc.). Also the ways in which loincloths of the Crucified were realized (it was later shortened) displays convergencies with the sculptures of the circle: it is a fine, flimsy fabric forming tiny ripples, locally ‘sticking’ to the body making it more explicit. One can notice analogies in the way the fabric is arranged in the Madonna of Lubieszewo (on her hip and leg), in the figure of St. Peter of Kraplewo (hanging coattail motif ) and in others. In view of those similarities, the crucifix of Starogard Gdański should be dated the way Clasen did – to the fourth quarter or the end of 14th century. The mentioned analogies make Clasen’s thesis plausible, while at the same time – in view of the fact that it would be the only preserved monumental crucifix linked to that artistic circle in Prussia – they enliven the discussion on the scale and the character of the phenomenon which was the so-called Madonnas on a Lion circle.